2021
DOI: 10.1177/1932296821997851
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in Telemedicine Use for Subspecialty Diabetes Care During COVID-19 Shelter-In-Place Orders

Abstract: Background: During the COVID-19 pandemic, telemedicine use rapidly and dramatically increased for management of diabetes mellitus. It is unknown whether access to telemedicine care has been equitable during this time. This study aimed to identify patient-level factors associated with adoption of telemedicine for subspecialty diabetes care during the pandemic. Methods: We conducted an explanatory sequential mixed-methods study using data from a single academic medical center. We used multivariate logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 10 publications
2
52
1
Order By: Relevance
“…During the COVID-19 pandemic, populations with health disparities are the same as those that are having difficulty accessing virtual health care. 5 Access barriers include an absence of health insurance and concerns about personal privacy, not having the necessary hardware and software, and the use of language that is not culturally congruent or inclusive. Affordability of health care is also a personal construct balancing the individual cost and time burden versus the perceived return on this investment.…”
Section: Principles For Virtual Health Care To Deliver Real Equity In Diabetesmentioning
confidence: 99%
“…During the COVID-19 pandemic, populations with health disparities are the same as those that are having difficulty accessing virtual health care. 5 Access barriers include an absence of health insurance and concerns about personal privacy, not having the necessary hardware and software, and the use of language that is not culturally congruent or inclusive. Affordability of health care is also a personal construct balancing the individual cost and time burden versus the perceived return on this investment.…”
Section: Principles For Virtual Health Care To Deliver Real Equity In Diabetesmentioning
confidence: 99%
“…Both initiation of telehealth and rapid increases in telehealth appointments due to the COVID-19 pandemic have been seen, but disparities exist in patient utilization of telehealth [2,[4][5][6][7]. Several studies have found that older patients, non-English speaking patients, and patients with public insurance were less likely to use telehealth as compared to in-person visits [4,5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Both initiation of telehealth and rapid increases in telehealth appointments due to the COVID-19 pandemic have been seen, but disparities exist in patient utilization of telehealth [ 2 , 4 7 ]. Several studies have found that older patients, non-English speaking patients, and patients with public insurance were less likely to use telehealth as compared to in-person visits [ 4 , 5 , 7 – 9 ]. These disparities could be due to differences in the patient populations; for instance, older and unstably housed patients and those with low broadband access are less likely to use telehealth, particularly video visits, compared to younger patients and those with higher income [ 4 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 17 ] Language can also be a barrier for non-English speakers. In a cross-sectional analysis of primary care patients in California from 2015 to 2016, those with limited English proficiency were 40% less likely to use telehealth, suggesting that interpreter services need to be integrated into telehealth care [ 50 , 51 ].…”
Section: Telehealthmentioning
confidence: 99%